2003
DOI: 10.1017/s002211200300466x
|View full text |Cite
|
Sign up to set email alerts
|

The structure of fine-scale scalar mixing in gas-phase planar turbulent jets

Abstract: Fine-scale scalar mixing in gas-phase planar turbulent jets is studied using measurements of three-component scalar gradient and scalar energy dissipation rate fields. Simultaneous planar Rayleigh scattering and planar laser-induced fluorescence, applied in parallel planes, yield the three-dimensional scalar field measurements. The spatial resolution is sufficient to permit differentiation in all three spatial directions. The data span a range of outer-scale Reynolds numbers from 3290 to 8330. Direct measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
87
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 37 publications
12
87
1
Order By: Relevance
“…Our data show that the scale l max follows now the same dependence with Reynolds number as the Kolmogorov scale, i.e. l max ∼ R −3/2 λ This result is similar to finding in [10,11] for Sc ∼ 1 and does not change for Sc ≫ 1.…”
Section: Fig 1: (Color Online)supporting
confidence: 89%
See 1 more Smart Citation
“…Our data show that the scale l max follows now the same dependence with Reynolds number as the Kolmogorov scale, i.e. l max ∼ R −3/2 λ This result is similar to finding in [10,11] for Sc ∼ 1 and does not change for Sc ≫ 1.…”
Section: Fig 1: (Color Online)supporting
confidence: 89%
“…Experimental studies on the geometry of scalar dissipation fields are very challenging since gradients have to be measured and only a few exist [10,11]. Figure 1 shows a two-dimensional (2D) slice cut through a DNS snapshot of ǫ θ (x, t).…”
mentioning
confidence: 99%
“…Su & Clemens 2003). Scalar dissipation measurements have been used to probe fine-scale mixing in canonical turbulent flows (Buch & Dahm 1996, 1998, constrain combustion models with turbulent jets (Su & Clemens 2003), and understand passive-scalar mixing in isotropic turbulence (Eswaran & Pope 1988;Girimaji 1992). We compute χ from the scalar fields using the numerical approach described in Buch & Dahm (1996).…”
Section: Scalar Dissipation Rate Fields and Mechanisms Of Mixingmentioning
confidence: 99%
“…In both regimes it was found that strained, laminar, sheet-like diffusion layers comprised much of the scalar dissipation rate fields. Scalar concentration measurements were obtained by Su & Clemens (2003) in turbulent jets using two parallel laser sheets with Rayleigh scattering and laser-induced fluorescence. Here the spatial derivative of the scalar field was computed in all three directions, permitting more accurate estimation of the scalar dissipation rate field.…”
Section: Introductionmentioning
confidence: 99%
“…The pdf of the (conditional) scalar dissipation rate has been largely assumed to follow a lognormal distribution, whose mean and variance enter in models of turbulent combustion. However, many measured pdf ( χ) show a difference to the lognormal distribution at both low and high values of χ in isothermal 17,[30][31][32] and reacting flows. 24,[27][28][29] The pdf typically has longer tails for low dissipation rate values and falls-off faster at high dissipation rate values, compared to the lognormal distribution.…”
Section: Introductionmentioning
confidence: 95%